β-Arrestin-mediated PDE4 cAMP phosphodiesterase recruitment regulates β-adrenoceptor switching from G(s) to G(i) - Baillie, George S. (The National Academy of Sciences, 2003)
Phosphorylation of the β(2) adrenoreceptor (β(2)AR) by cAMP-activated protein kinase A (PKA) switches its predominant coupling from stimulatory guanine nucleotide regulatory protein (G(s)) to inhibitory guanine nucleotide regulatory protein (G(i)). β-Arrestins recruit the cAMP-degrading PDE4 phosphodiesterases to the β(2)AR, thus controlling PKA activity at the membrane. Here we investigate a role for PDE4 recruitment in regulating G protein switching by the β(2)AR. In human embryonic kidney 293 cells overexpressing a recombinant β(2)AR, stimulation with isoprenaline recruits β-arrestins 1 and 2 as well as both PDE4D3 and PDE4D5 to the receptor and stimulates receptor phosphorylation by PKA. The PKA phosphorylation status of the β(2)AR is enhanced markedly when cells are treated with the selective PDE4-inhibitor rolipram or when they are transfected with a catalytically inactive PDE4D mutant (PDE4D5-D556A) that competitively inhibits isoprenaline-stimulated recruitment of native PDE4 to the β(2)AR. Rolipram and PDE4D5-D556A also enhance β(2)AR-mediated activation of extracellular signal-regulated kinases ERK1/2. This is consistent with a switch in coupling of the receptor from G(s) to G(i), because the ERK1/2 activation is sensitive to both inhibitors of PKA (H89) and G(i) (pertussis toxin). In cardiac myocytes, the β(2)AR also switches from G(s) to G(i) coupling. Treating primary cardiac myocytes with isoprenaline induces recruitment of PDE4D3 and PDE4D5 to membranes and activates ERK1/2. Rolipram robustly enhances this activation in a manner sensitive to both pertussis toxin and H89. Adenovirus-mediated expression of PDE4D5-D556A also potentiates ERK1/2 activation. Thus, receptor-stimulated β-arrestin-mediated recruitment of PDE4 plays a central role in the regulation of G protein switching by the β(2)AR in a physiological system, the cardiac myocyte.